Risk identification for early warning of bleeding among mothers during childbirth - Sulastri Sulastri; Tongku Nizwan Siregar; Muhammad Adlim; Hasanuddin Hasanuddin; Gholib Gholib; Lilis Suryani (Intelektual Pustaka Media Utama, 2023)
The study was conducted using the observational method. It assessed blood loss using a calibrated measuring cup every 15 minutes in the first hour after delivery and every 30 minutes for the next hour. The results of the analysis showed that the modelling of early warning identification in laboring mothers is influenced by the age and weight of the mother, which is at a significance of 10%. A major warning sign is an increase in blood pressure rate in the third stage of labor which begins 15 minutes from the start of bleeding, and is categorized as dangerous when the blood volume reaches 600 mL. Therefore, every mother in labor must be monitored regularly and continuously and early warning signs must be taken into account. There is no safe time in cases of blood loss. It is very important to identify the risks in a timely manner to identify the source of bleeding so that it can be handled quickly and appropriately in order to prevent complications and maternal death due to postpartum haemorrhage (PPH). Implication, effective and optimal identification in clinical practice should be evidence-based in order to better determine whether or not intervention is needed to prevent blood loss after childbirth.